Spontaneous inguinal enterocutaneous fistula, as an exceptional complication of incarcerated Richter’s hernia: A case report - Aliou, Zabeirou Oudou; Mourad, Badri; Tarek, Souiki; Karim, İbn Majdoub and Imane, Toughrai and Khalid, Mazaz (Journal of Surgery and Medicine, 2019)
Richter’s hernia may be defined as an abdominal hernia in which only part of the circumference of the bowel wall is entrapped and strangulated in the hernial orifice. It occurs at various positions with femoral ring being the most common. As the bowel continuity is maintained, the patients usually do not have intestinal obstruction. The spontaneous enterocutaneous fistula is a rare complication of inguinal Richter’s hernia. We report a case of a 75 year old female patient with enterocutaneous fistula which occurred spontaneously in the right inguinal region. Abdominal computed tomography scan confirmed the diagnosis of enterocutaneous fistula. We performed a right celiotomy with resection and primary anastomosis of the fistulous bowel. Patient recovered uneventfully without any complications or recurrence.